Diversity and phylogeny of basidiomycetous yeasts from plant leaves and soil: Proposal of two new orders, three new families, eight new genera and one hundred and seven new species - Li, A. H. (2021)
Funding Information: We thank Prof. Jian-Yun Zhuang for his advice on nomenclatural matters. We thank Dr. Alexander Idnurm for his kindly providing the sequences and informations of strain IAM13481 and his critical comments for this manuscript, Dr. Aleksey Kachalkin for his sharing the physilogical data of strain KBP Y-5548 and Masako Takashima for her sharing the physilogical data of strain TY-217. We also thank Ana Pontes and Cl?udia Carvalho for editing illustrations of Kondoa myxariophila and for ITS sequencing, respectively. This study was supported by grants No. 31570016 from the National Natural Science Foundation of China (NSFC) and national project on scientific groundwork No. 2014FY210400 from the Ministry of Science and Technology of China. The authors are solely responsible for the content of this work.